Vicarious Nucleophilic Substitution of Hydrogen: An Excellent Tool for Porphyrin Functionalization - Ostrowski, Stanisław; Mikus, Agnieszka (SynOpen, 2025)
This graphical review addresses the functionalization of porphyrin derivatives. Simple porphyrin modifications (by introduction of an electron-withdrawing group, e.g., NO2, CO-R, into parent porphyrin system or complexation of the core ring with a highly electronegative unit, e.g., SnCl2) afford valuable intermediates in this area of chemistry. They are useful materials for further transformations, as such modifications increase the electrophilic character, thus allowing a broad spectrum of subsequent reactions. Such reactions are often utilized in the first steps of designed syntheses, leading to attractive and useful target porphyrin-like compounds featuring a high degree of complexity. In this regard, the vicarious nucleophilic substitution of hydrogen (VNS) has become one of the methods of choice. Specifically, it involves addition of a carbanion, bearing a leaving group X at the reactive center, to an electrophilic arene at positions occupied by hydrogen to form a σH-adduct. Subsequent base-induced β-elimination of HX then gives the product of nucleophilic substitution of hydrogen. This approach enables the synthesis of numerous porphyrins bearing up to ten new substituents on the meso-aryl rings (attached to positions 5, 10, 15, and 20) and up to six substituents at the β-positions. This graphical review is the first comprehensive account concerning VNS reaction in porphyrins.
Keywords: porphyrins; vicarious nucleophilic substitution of hydrogen; carbanions; complexes; nitro group; meso-aryl- and β-functionalization